Onbody diversity and angle-of-arrival measurement using a pattern switching antenna - Kamarudin, Muhammad R. (Institute of Electrical and Electronics Engineers, 2009)
Diversity is one of the methods to overcome the multipath effect in the mobile environment. A pattern diversity antenna with four beams was used to investigate the diversity performance in the onbody environment. A switched diversity combining method-switch-and-stay strategy - was used to analyze the data. Finding an angle of arrival (AoA) of different multipath components is very useful since it allows optimization of the base-station antenna radiation patterns and can be used to locate and track the handsets that operate in a particular cell. Similarly, in onbody communications, knowing the AoA enables determining the position of the antennas relative to each other and supports the design of antennas with optimized radiation patterns. Diversity and AoA measurements have been performed for five randomly movements body channels. In diversity measurements, the antenna beams are switched quickly considerably faster than the body movements. The results show that significanct gains are achieved for non-line-of-sight channels and no gain is obtained for the LOS channel since the signal is received by the same beam during the measurement. During AoA measurements, the 2-D process is chosen in which the angles are in a 2-D plane around the ground plane of the antenna. The main propagation paths of the transmitted signal are limited to a limited interval of the AoA range. These AoA estimates for onbody propagation channels can be used for designing better fixed beam and pattern diversity antennas.